Analisis Kelayakan Finansial Usaha Ternak Ayam Kampung Super (Studi Kasus pada Peternakan Suparlan di Desa Jojog Kecamatan Pekalongan Kabupaten Lampung Timur) - Fikri Fathurahman Aziz (Wahana Peternakan, 2019)
This study aims to analyze financially (net present value, revenue cost ratio, internal rate of return, break event point, return on investment and payback period) feasibility of kampung super chicken farming Mr. Suparlan in Jojog village, district Pekalongan, East Lampung regency. The data used in the form of quantitative and qualitative data sourced from the primary data and secondary data which is then analyzed descriptively. Based on the analysis, it is known that kampung super farm is financially feasible to cultivate. This is indicated by the positive value of net present value (NPV) of Rp 186,568,517, revenue ratio (RCR) 1.59, internal rate of return (IRR) of 135.82%, return on investment (ROI) of 43%, and the value of payback period (PP) of 0.50. Keywords: financial feasibility, kampung chicken, chicken farm